MANAJEMEN STRATEGIK BERUPA IDENTIFIKASI SWOT DALAM PERENCANAAN PENDIDIKAN PADA MADRASAH NEGERI - Eko Sulistiyanto; Chusnul Chotimah (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
This study aims to identify educational administrative planning based on SWOT identification. This research uses a Library Research approach. SWOT analysis is an instrument for preparing strategic planning in an organization by analyzing Strenghts, Weaknesses, Opportunities, and Threats. Planning is a process of determining the right future actions, through a sequence of choices, taking into account the available resources. Planning documents in Madrasah consist of 2 (two) planning documents in the form of a 5 (five) yearly Strategic Plan (Renstra) and a 4 (four) yearly Madrasah Work Plan (RKM). SWOT analysis is very important to be carried out by madrasahs when preparing madrasah planning. Based on the findings of the research results, researchers suggest that each state madrasah identifies and analyzes existing opportunities, according to the conditions of each madrasah.